Distress-based evidential reasoning method for pavement infrastructure condition assessment and rating. Issue 4 (21st March 2021) - Abu Dabous, Saleh; Zeiada, Waleed; Al-Ruzouq, Rami; Hamad, Khaled; Al-Khayyat, Ghadeer
ABSTRACT: Pavement condition rating is an essential step in pavement management, as it provides the basis for maintenance decisions and budget allocations. The pavement deterioration process is stochastic in nature because several types of distress usually affect performance of a pavement structure. Hence, the deterministic number-based condition indices used to rate pavement condition are not sufficient. This paper introduces the evidential reasoning (ER) theory to the area of pavement condition assessment and discusses a distress-based condition assessment method using an evidential reasoning approach. The proposed pavement assessment method utilises a condition matrix to assess the basic probability of pavement condition based on extent and severity of different distresses identified in a pavement structure. The Dempster–Shafer theory of evidence is used to aggregate evidence into an overall 'belief value' reflecting the probable condition assessment of the pavement structure. The proposed ER method holds specific advantages over other available condition assessment methods and has potential to enhance the condition rating process. A case study is used to illustrate the proposed method and to validate its results. Based on the obtained results, the proposed method facilitates eliminating inconsistency in subjective judgment processes and produces a robust pavement condition rating.